Non-polynomial Cubic Spline Method for the Solution of Second-order Linear Hyperbolic Equations - Çağlar, Nazan (My University, 2021)
Second-order linear hyperbolic equations are solved by using a new three level method based on nonpolynomial spline in the space direction and Taylor expansion in the time direction. Numerical results reveal that three level method based on non-polynomial spline is implemented and effective
Keywords: Second-order linear hyperbolic equation; Non-polynomial cubic spline